1993
DOI: 10.1002/eji.1830230329
|View full text |Cite
|
Sign up to set email alerts
|

RANTES and related chemokines activate human basophil granulocytes through different G protein‐coupled receptors

Abstract: Chemotactic cytokines related to interleukin-8 (IL-8; CXC-chemokines) or monocyte chemotactic protein-1 (MCP-1; CC-chemokines) have been shown to stimulate human basophils, and are considered important tissue-derived mediators of inflammation. We have studied the effects of four CC-chemokines and show that MCP-1, RANTES (regulated on activation, normal T expressed and secreted) and macrophage inflammatory protein-1 alpha (MIP-1 alpha) are potent basophil agonists inducing a rapid change of cytosolic free calci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
139
0
1

Year Published

1994
1994
2017
2017

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 199 publications
(147 citation statements)
references
References 35 publications
7
139
0
1
Order By: Relevance
“…We have previously found eosinophil shape change induced by chemokines to be pertussis toxin sensitive (I. Sabroe, unpublished data). Other studies have shown basophil responses to chemokines including RANTES, MCP-1, and IL-8 to be similarly sensitive to pertussis toxin (22,(52)(53)(54).…”
Section: Discussionmentioning
confidence: 93%
“…We have previously found eosinophil shape change induced by chemokines to be pertussis toxin sensitive (I. Sabroe, unpublished data). Other studies have shown basophil responses to chemokines including RANTES, MCP-1, and IL-8 to be similarly sensitive to pertussis toxin (22,(52)(53)(54).…”
Section: Discussionmentioning
confidence: 93%
“…Among the chemokines detected in airways of patients with allergic asthma is monocyte chemotactic protein (MCP)-1 (16). Various roles have been attributed to MCP-1 in promoting allergic responses, including recruitment of basophils (17) and clumping of mast cells (18), IgE-independent induction of basophil (17) and mast cell (18) histamine release, chemotaxis of T cells (19), and enhancement of polarization of naive T cells to IL-4-producing Th2 cells (20,21). Further evidence that MCP-1 may play a role in allergic asthma can be found in studies that observe that MCP-1 immunoneutralization resulted in reduction in AHR, pulmonary inflammation, and production of lymphocyte-derived inflammatory mediators in allergen-challenged animals (22)(23)(24).…”
mentioning
confidence: 99%
“…Most of the cellular responses following exposure of the cells to chemotactic agonists and all the signaling events known to date are induced very rapidly and only transiently generally returning to baseline within a few minutes. At sufficiently high concentrations of the agonist, there is also a complete homologous receptor desensitization of the corresponding chemoattractant receptor, preventing further signal transduction and a second cellular response upon repeated stimulation (4,5,7,8). Despite the desensitization for these rapid and transient responses, basophils exposed to C5a and IL-3 produce the cytokines IL-4 and IL-13 and continuously release leukotriene C4 (LTC4) during a culture period of 18 h (9, 10), indicating that some components of the signaling pathway may be long-lasting and/or that the C5aR can be continuously engaged by the ligand activating a pathway that is not desensitized.…”
mentioning
confidence: 99%